Identification of Prosocial Behaviour and Religious Values through Habituation Method at RA Kusuma Dewi - Yuliawati, Fatimah Nur; Putri, Leni Alifa; Fauziyah, Nur (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, 2023)
In this current era, many children do not understand and unfamiliar with prosocial behaviour according to the beliefs of their own religion. There are still many children who have not been able to internalize teir religion values in everyday life. The purpose of this study to develop prosocial behaviour and increase faith through the habit of worship which is carried out every Friday. The method of research is a qualitative approach using interview, observation, and documentation methods. The result of this research is habituation act, every Friday it is carried out through sharing activities and the practice of prayer together can develop prosocial behaviour and increase religious values in early childhood in accordance with the Child Development Achievement Level Standards (STPPA).